DEVELOPING A CEFR-BASED COMIC FOR ENGLISH LITERACY LEARNING AT HIGH SCHOOL STUDENTS IN CIREBON - Qori, Qorina Awa Rosi; Farouk Imam Arrasyid; Haira Rizka (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2025)
This study aims to develop a comic-based CEFR learning media for English literacy learning for high school students in Cirebon. This study are quantitative and qualitative research type with the ADDIE model. The sample in this study was an English teacher at the school concerned and 5 high school students in grade 10. Data collection was carried out by interview and documentation. Data were analyzed by data reduction, data presentation, and verification. The results of the study can show that the comic-based CEFR product is declared very feasible and ready to be implemented for English literacy learning for high school students in Cirebon.